Implementing recommendations for routine mismatch repair (MMR) immunohistochemistry (IHC) testing of endometrial cancer and subsequent patient management - Jo Morrison; Mohamed Shawky; Maria Murrey (BMJ Open Quality)
Lynch syndrome is associated with an increased risk of cancer, including endometrial cancer. We audited the introduction of a nurse-led testing and management pathway for Lynch syndrome. All 191 patients diagnosed with endometrial cancer at Somerset NHS Foundation Trust between January 2022 and December 2023 were tested for mis-match repair (MMR) protein immunohistochemistry; germline testing was offered to all 13 who were eligible. Seven patients were diagnosed with Lynch syndrome; all were referred for bowel screening and Helicobacter pylori testing. Information about prophylactic aspirin recommendations was missing for 3/7 patients. We established an effective, nurse-led Lynch syndrome testing pathway, in line with national guidelines.